Milk production, consumption and marketing in Eastern Region of India: A Farm Level Analysis - Kumari, Binita; Chandel, B.S.; Kumari, Tulika; Lal, Priyanka (Indian Journal of Dairy Science, 2022)
The present study was undertaken in the eastern region of India comprising of the states of Bihar, West Bengal and Jharkhand with the objective to determine milk production, consumption and marketed surplus at farm level (in continuation of the above line) The study found that, inspite of low dairy development in the region, milk production and productivity was considerably high among the sample households. An average dairy household was producing about 36 litre of milk per day having average productivity of 10 litre per day per animal which was significantly higher than national averages. The milk was drawn more from crossbred cows on Small households and from local cow and buffalo on large households. The highest milk productivity on large farms emphasize for removing the resource limitation and promote better feeding and management practices among small and medium herd size categories. The consumption of liquid milk among producer households was 207 gm per day per capita which was higher than per capita availability in the region. Of the 10 per cent of the milk production retained at household level, 40 per cent was consumed as liquid milk and 60 per cent was converted into milk products. The later share was higher among small herd size category catering to the rural non-milk producing households. The halwais/ dudhiyas/private dairies were the major marketing channel counting for 61 per cent of the total marketed surplus and only 21 per cent of the milk was sold through cooperatives. The share of milk sold through later channel by small farmers was still lower (10%) inspite of the fact that the marketed surplus per household was substantially higher (24.02 L/day). Â Â An analysis in to the factor affecting marketed surplus found that being membership of dairy cooperatives had the highest influence on marketed surplus of small farms. Â